Experimental Study of a Thermal Plume Evolving in a Confined Environment: Application to Fires Problems - T. Naffouti; M. Hammami; M. Rebay; R.B. Maad (Journal of Applied Fluid Mechanics, 2009)
We propose to study the natural convection flow resulting from the interaction of a fire with walls that surround it. Indeed, when a fire occurs in a tunnel or in a tower block, it creates a thermal plume causing a heating of the neighbouring walls. This heating by thermal radiation of the walls creates a phenomenon of thermosiphon which interacts with the plume. To study this flow we simulated the problem at the laboratory where we placed a rectangular source heated by Joule effect at the entrance of an open-ended vertical canal. The flow visualization by laser plan and the exploration of the thermal and dynamic fields inside the canal enabled us to describe the flow structure. In order to better characterize this flow, we carried out a fine analysis by studying the spectra of temperature fluctuations. This spectral analysis allowed us to clarify the energetic evolution of the vortexes during their ascension and verify some known spectral laws.